DIY. The Recipe for Polish Language Lesson for Foreigners with Elements of Art Therapy (by the Example of Gratitude Journal) - Kownacka, Patrycja (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
This article is dedicated to the use of selected art therapy methods and techniques in Polish as a foreign language lessons. It consists of theoretical and practical parts. The first part presents the functions of art therapy in education. The selected art therapy methods are characterized and examples of their application in Polish language didactics are provided. Next, the concept of pilot workshops dedicated to the use of a gratitude journal created using the scrapbooking technique in Polish as a foreign language lessons is presented. The article concludes by presenting feedback from the project participants, who highlighted the impact of positive emotions associated with creative work on enhancing the effectiveness of the educational process (learning the Polish language). The presented didactic proposals and research fit in the trend of studies on the well-being of foreigners learning Polish.